English Curricula in ASEAN Selected Countries: A Comparative Study - Nuraeni, Cicih; Priadi, Agus; Lengkanawati, Nenden Sri (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
To ensure the development of the ASEAN Economic Community, ASEAN countries must use English as the common language of business, education, and social life. Indeed, several ASEAN nations have embraced English as a second language, but many also consider English to be a foreign language. Especially in the field of education, adjustments to the English curriculum have also been implemented. The curriculum is designed to meet the educational goals of a nation as a set of plans and instructions regarding objectives, content, and learning materials, as well as the methodology used as a direction for completing learning activities. This study compares the English curricula in ASEAN selected countries at the university level. A research-based paper was used as the research approach. The findings indicated that the English curriculum is implemented differently in the four ASEAN nations of Indonesia, Thailand, Vietnam, and Malaysia. English goals and objectives, materials and content, method, and assessments are all compared as a foundation for curriculum development of university level in Indonesia. This study suggests that more research be conducted to compare the English curricula of countries that use English as a Second Language (ESL) so that it might be adopted by nations that use English as a Foreign Language (EFL).